Transformative Experiences in English Microteaching: Educational Inquiry into Pedagogical Adjustment, Reflection, and Skill Refinement - Stevani, Margaret; Martiningsih, Evi; Panduwinata, Tiara; Rais, Rinovian; Wardani, Happy Kusuma; Saragi, Alexander Adrian; Nurmayana, Nurmayana; Dalimunte, Nurul (Journal of English Language and Education, 2026)
This qualitative study investigated the transformative experiences of pre-service English teachers during microteaching at two private universities in North Sumatra, Indonesia. Involving a purposive sample of 14 Indonesian pre-service teachers, data were collected through teaching journals, classroom observations, audio-visual recordings, and stimulated recall interviews. Thematic analysis was used, guided by Vygotsky’s ZPD, Schon’s reflective practice, and Wenger’s comunicative practices theory. Findings revealed shifts from routine teaching to adaptive, student-centered strategies characterized by pedagogical adjustment, reflective awareness, and instructional skill refinement. Participants showed increased sensitivity to timing, language accuracy, emotional climate, and sociocultural engagement. The study highlighted microteaching as a dynamic platform for identity formation and pedagogical growth. The research offered critical insights into teacher development and suggested future studies with broader contexts to capture sustained transformation in English education.